Xylopia aethiopica Attenuates Oxidative Stress and Hepatorenal Damage in Testosterone Propionate-Induced Benign Prostatic Hyperplasia in Rats - Ibiam, Udu A.; Uti, Daniel E.; Ejeogo, Chris C.; Orji, Obasi U.; Aja, Patrick M.; Nwamaka, Ezeaani N.; Alum, Esther U.; Chukwu, Chukwuma; Aloke, Chinyere; Itodo, Matthew O.; Agada, Samuel A.; Umoru, Grace U.; Obeten, Uket N.; Nwobodo, Valentine O.G.; Nwadum, Solomon K.; Udoudoh, Mfon P. (Journal of Health and Allied Sciences NU, 2024)
Objectives Xylopia aethiopica (XAE), commonly known as African pepper or Ethiopian pepper, is a plant native to West Africa and known for its aromatic and medicinal properties. It was used to investigate the antioxidative, antihepatotoxic, and antinephrotoxic potentials of XAE in benign prostatic hyperplasia (BPH) in Wister albino rats.Methods The proximate, and vitamin composition, oxidative stress indicators, and indices of kidney and hepatic functions were performed by standard methods.Results The proximate composition of the XAE leaf showed varied concentrations of Mg, Ca, Na, Zn, Se, and Cl, as well as vitamins A, E, B3, D, C, K, B2, and Bi. The activities of catalase glutathione, superoxide dismutase, malondialdehyde levels, K, Na, Cl−, urea, uric acid, and creatinine in the kidney were increased in testosterone propionate (Tp)-induced BPH compared with the control groups. Total protein levels significantly decreased in Tp-induced BPH compared with XAE-treated groups increased on XAE treatment. The aspartate transaminase, alanine aminotransferase, and alkaline phosphatase activities were not significantly different in Tp-induced BPH, XAE, and normal controls.Conclusion The study revealed that XAE can be used in the management of oxidative stress and hepatorenal damage in BPH condition.
Keywords: benign prostatic hyperplasia; Xylopia aethiopica; oxidative stress; hepato-renal damage; minerals